A Comparison between Primary and Secondary Flap Coverage in Extraction Sites: A Pilot Study. - Aladmawy, Majdi. (2017)
Abstract: Aim and Hypothesis: Once a tooth is extracted from its socket, bone loss with dimensional changes occurs within the first 6 months. Bone augmentation with the use of a barrier membrane can be used to preserve bone loss. This technique is called ridge preservation, and it is the focus of the current research. The primary aim of this study was to evaluate the bone dimensional changes following extraction and ridge preservation with primary coverage (closed flap technique-CFT) compared to healing with secondary intention (open flap technique-OFT). We hypothesized that the CFT would have more potential than the OFT in maintaining vertical bone height due to less susceptibility from infection and inflammation. The secondary aim was to evaluate patients' self-report of postoperative pain. Materials and Methods: This study had 10 patients (10 sites CFT and 10 sites OFT) with at least 2 sites planned: extraction and ridge preservation on one site and on the contra-lateral site tooth/teeth of the same arch, e.g. extractions of the maxillary right canine and the maxillary left canine. Following the extractions, both sites had ridge preservation and non-resorbable membranes. The CFT had the flap released buccally and coronally positioned covering the non-resorbable membrane, while OFT had no release of the buccal flap, leaving the membrane exposed. Standardized measurements utilizing a stent and a probe were used to evaluate the dimensional changes of the alveolar ridge at 4 sites: Center Height (CH), Buccal Height (BH), Coronal Width (CW) at 3 mm apical to the buccal crest, and Apical width (AW) at 5 mm apical to the buccal crest. In addition, the difference in keratinized tissue width (KTW) between both sites was recorded at baseline and at six months. The data were analyzed with a Wilcoxon signed-rank test. Results: Statistical significance within a given group was found in both CFT and OFT when comparing baseline to 6 months for CH (mean difference of 8.1 mm, SD =1.9, median of 8mm, IQR of 3 p = 0.005 for CFT and 7.5 mm, SD= 1.8, median of 7 mm, IQR of 3, p = 0.005 for OFT). CFT yielded statistical significance in BH compared to baseline within group at 6 months; however, there was no statistically significant difference among groups in CH, BH, CW, or AW when comparing baseline to 6m differences. The KTW of the OFT group was significantly higher than that of the CFT (mean of 1.7 mm, SD= 0.6, median of 2, IQR of 1, p = 0.004). In contrast to CFT, OFT had significantly lower pain VAS scores at 24 hours following extraction (mean difference of 1.1 mm, SD= 0.5, median of 1 and IQR of 0 vs. mean of 3, SD= 0.8, median of 3, IQR= 2 respectively, p = 0.006). No statistical significance was found between groups at the 2 weeks follow up visit. Conclusions: There was a statistical significance gain in bone height in both groups from the apical portion of the socket to the CH stent point in the center of the socket when comparing baseline to 6 months. CFT had a statistical significance in BH unlike the baseline within group at 6 months. However, there was no statistical significance between the open and closed flap techniques following extraction and ridge preservation with a non-resorbable membrane at center, buccal, 3mm, and 5mm locations. Leaving the flap open led to a wider band of keratinized tissue and less pain compared to closing the extraction socket with a flap.; Thesis (M.S.)--Tufts University, 2016.; Submitted to the Dept. of Periodontology.; Advisor: Yong Hur.; Committee: Bjorn Steffensen, Paul Levi, Matthew Finkelman, Yumi Ogata, and Wai Cheung.; Keywords: Dentistry, Health sciences, and Higher education.